2019
DOI: 10.1128/iai.00822-18
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pyrin Dephosphorylation and Inflammasome Activation in Macrophages as Triggered by the Yersinia Effectors YopE and YopT

Abstract: Pathogenic Yersinia species deliver Yop effector proteins through a type III secretion system into host cells. Among these effectors, YopE and YopT are Rhomodifying toxins, which function to modulate host cell physiology and evade immune responses. YopE is a GTPase-activating protein (GAP) while YopT is a protease, and they inhibit RhoA by different modes of action. Modifications to RhoA are sensed by pyrin, which, once activated, assembles a caspase-1 inflammasome, which generates cytokines such as interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…YopE GAP and YopT protease activities were demonstrated to trigger the pyrin inflammasome by infecting LPS‐primed BMDMs with Yersinia strains in which the yopE or yopT genes were mutated in a yopM mutant background 16,17,18,47 . Introduction of mutations that inactivated the two genes or the catalytic activities of the gene products alone or in combination demonstrated that YopE GAP has a dominant role in triggering activation of pyrin (Figure 1, Step 12) 16,17,18,47 . Pyrin activation triggered by YopT protease activity (Figure 1, Step 13) can only be detected in the absence of YopE in LPS‐primed BMDMs infected with Y. pseudotuberculosis 16,18 .…”
Section: The Pyrin‐yersinia Effector Interactionmentioning
confidence: 99%
See 4 more Smart Citations
“…YopE GAP and YopT protease activities were demonstrated to trigger the pyrin inflammasome by infecting LPS‐primed BMDMs with Yersinia strains in which the yopE or yopT genes were mutated in a yopM mutant background 16,17,18,47 . Introduction of mutations that inactivated the two genes or the catalytic activities of the gene products alone or in combination demonstrated that YopE GAP has a dominant role in triggering activation of pyrin (Figure 1, Step 12) 16,17,18,47 . Pyrin activation triggered by YopT protease activity (Figure 1, Step 13) can only be detected in the absence of YopE in LPS‐primed BMDMs infected with Y. pseudotuberculosis 16,18 .…”
Section: The Pyrin‐yersinia Effector Interactionmentioning
confidence: 99%
“…Introduction of mutations that inactivated the two genes or the catalytic activities of the gene products alone or in combination demonstrated that YopE GAP has a dominant role in triggering activation of pyrin (Figure 1, Step 12) 16,17,18,47 . Pyrin activation triggered by YopT protease activity (Figure 1, Step 13) can only be detected in the absence of YopE in LPS‐primed BMDMs infected with Y. pseudotuberculosis 16,18 . No role for YopT in activating pyrin could be demonstrated in LPS‐primed BMDMs infected with Y. pestis 17,47 .…”
Section: The Pyrin‐yersinia Effector Interactionmentioning
confidence: 99%
See 3 more Smart Citations